Unconventional research in a conventional practice, a case study - Mote, Miranda (ARCC Conference Repository, 2018)
The primary subject of this paper is a historically conventional architectural practice that has enjoyed success with clients and projects in the Midwest. Currently, the firm's demographics and practice are typical to the industry nationwide. New leadership have emphasized the necessity of research and invested in employee centered, professional, and academic programs. The board of directors has diligently developed and supported programs that foster productive partnerships with academia. The research and professional development programs described below are not unique to this firm. I will explore the potential and realized value they bring to this mid-sized corporate architectural firm, their project work and their respective academic partners. The following programs will be subjected to analysis and critique: 1. Continuing Education: Programming supports traditional classroom learning as well as an in-house research fellowship offered to enable employees to engage in research as a project.; 2. University Endowment: The endowed position will offer studios and lectures that encourage collaborative learning between practicing and future designers interested in sustainable design in Cincinnati.; 3. Executive Education: the firm has hired Xavier University as a professional consultant. Xavier University offers professional services to private clients utilizing its academic resources in their School of Business. Objective: This case study will measure the success of research and professional development programs in terms of firm recruitment, financial return, and improved professional culture. The case study will conclude with recommendations for improved and continued partnership between practice and the academy and how research can be comfortably situated within the confines of conventional practice.